Regulating Ecosystem Services of forests in ten Italian Metropolitan Cities: Air quality improvement by PM10 and O3 removal. (August 2016) - Manes, F.; Marando, F.; Capotorti, G.; Blasi, C.; Salvatori, E.; Fusaro, L.; Ciancarella, L.; Mircea, M.; Marchetti, M.; Chirici, G.; Munafò, M.
Highlights: The regulating ES provided by forests is analyzed in 10 Italian cities. The removal of O3 and PM10 is affected by forest cover. PM10 deposition on forests mainly depends on LAI. O3 absorption is mainly influenced by forest functional diversity. These findings can be useful to a nature-based urban sustainable management. Abstract: Urban and periurban forests, which are integrated within the concept of Green Infrastructure, provide important Ecosystem Services, including air purification. In this study, we quantified the Ecosystem Service of particulate matter (PM10 ) and Ozone (O3 ) removal from urban and periurban forests in ten metropolitan cities in Italy, and its total monetary value. In order to gain a better understanding of how Ecosystem Services can be regulated on a wider scale, the vegetation ecosystem types were grouped into Physiognomic-Structural Categories of Vegetation according to morphofunctional criteria. The pollution removal was mapped using a remote sensing and GIS approach, by applying a deposition model and a stomatal flux model. We estimated, for the ten metropolitan cities, an overall pollution abatement of 7150 Mg of PM10 and 30, 014 Mg of O3 in the year 2003, which was an extremely hot year. Our findings indicate that structural characteristics (i.e. Leaf Area Index) and functional diversity, linked to stomatal conductance, exert a marked influence on the provision of the regulating Ecosystem Services, whose total monetary value was estimated to be equal to 47 and 297 million USD for PM10 and O3 removal, respectively. This study represent the first national-scale assessment of the Ecosystem Services of air pollution removal in Europe, thus providing information that may be useful to stakeholders to manage Green Infrastructure more efficiently.